Urban Self-building Labour Cost Modelling In Cameroon - Manjia, Marcelline; Pettang, Chrispin; Abanda, Fonbeyin (Penerbit Universiti Sains Malaysia, 2011)
The critical housing shortage in some cities of developing countries such as Cameroon generates an ever-growing desire to increase the housing supply. Due to the complex legislature system of Cameroon, housing policies and high costs associated with the acquisition of housing from the formal sector, the majority of urban residents are resorting to what are termed “informal practices”, such as self-construction. This mode of housing provision, although diffcult, has become the dominant mode of housing provision within the construction sector of most developing countries. As an informal sector, practices are characterised by unclear accounting methods, including labour costing and by often-present sub-par management techniques, which lead to delays in the completion of some projects. To address these issues, a method of estimating labour cost based on a developed matrix model is presented in this paper. Through the introduction of a fnite dimensional vector space composed of standard tasks, the model presented directly relates the quantity of work to the labour cost. Application of this new approach to a case study in Cameroon shows how labour costs could be reduced by 37% compared to the simple matrix method examined by other researchers.